ILLEGAL ABORTION IN INDONESIAN MEDIA: A CONTENT ANALYSIS - Susiati, Susiati; Udasmoro, Wening; Saktiningrum, Nur (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2023)
Abortion is a complex issue. On the one hand, abortion is an illegal act according to positive law and is prohibited by religion in Indonesia. On the other hand, abortion is a shortcut to solving unwanted pregnancies by married and unmarried couples. This study aims to see how the media frames news about illegal abortion, how positive law regulates this act and what the triggers doing illegal abortion. This research is qualitative research with a content analysis approach. The results of the study show that the media tends to be neutral by not taking sides between the perpetrators and the victims. This research also reveals the fact that the high demand of the Indonesian people for an illegal abortion service is at least triggered by two things, the legal system, and social norms applied in Indonesia. The legal system prohibiting abortion in Indonesia is incapable to prevent and provide a deterrent effect against perpetrators of abortion criminalization. In addition, Indonesian society’s system of social norms is very sensitive to immoral cases, such as pregnancy out of wedlock. As a result, many pregnant women who are out of wedlock choose to hide their pregnancies and then secretly carry out illegal abortions